JURIDICAL ANALYSIS OF THE “STRONG” TRADEMARK DISPUTE BETWEEN HARDWOOD PRIVATE LIMITED AND PT UNILEVER INDONESIA TBK (A STUDY OF DECISION NUMBER 332 K/PDT.SUS-HKI/2021) - Geby Sabita Panjaitan; July Esther; Roida Nababan (RADJA PUBLIKA, 2026)
The “STRONG” trademark dispute between Hardwood Private Limited and PT Unilever Indonesia Tbk has led to overlapping ownership claims and divergent legal interpretations at different judicial levels. This research seeks to assess the implementation of the legal certainty principle for the initial trademark registrant and to evaluate the legal reasoning adopted by the Supreme Court in Decision Number 332 K/Pdt.Sus-HKI/2021 in light of Law Number 20 of 2016. Employing a normative legal research framework, this study applies qualitative analysis through statutory and jurisprudential approaches. The results indicate inconsistencies in applying the first-to-file doctrine, as the Supreme Court granted the trademark rights to PT Unilever by characterizing “Strong” as a descriptive common term that cannot be exclusively owned, notwithstanding Hardwood’s status as the earliest registrant. These findings underscore the importance of conducting thorough substantive examinations by the Directorate General of Intellectual Property during trademark registration to avoid overlapping rights. Additionally, there is a pressing need to reinforce regulations governing the use of common terms in trademarks to promote justice and legal certainty for prior registrants and to prevent monopolization of language in commercial practices. Keywords: Trademarks; Legal Certainty; Trademark Disputes